Image of the new vaccination obligation through the media. Issue 3 (16th January 2020) - Mitilian, Eva; Malli, Fady; Verger, Pierre
Abstract: Introduction: Vaccination campaigns always go hand by hand with controversies about their safety and usefulness. The widespread perception of vaccines as dangerous induces a decrease in the population immunization coverage, which led The French Ministry of Health to add 8 new mandatory vaccines to the 3 existing ones. The objective of this study is to analyze the information conveyed by the media and received by the French population about this new legislation. Method: The newspaper articles and television and radio programs were selected from the media with the highest audience rate from January 2016 to May 2018. They were analyzed according to the grounded theory, up to data saturation, with double coding. Results: The qualitative analysis included 38 written press articles, 18 radio programs and 18 television programs. After coding, several themes emerged. Discussions about the usefulness of vaccination, trust in vaccines, vaccination coverage, and the cost of measure were controversial in the media. Questions about ethics were also mentioned. The description of anti-vaccines by journalists and some doctors conveyed a negative image while reminding their strong mobilization through social media. The law and its implementation details were frequently reminded across the different media. Discussion-Conclusion: Traditional media give opposing views on immunization obligations. Vaccination is supported by a majority of doctors. Parents share their fears and concerns about vaccination and its adverse effects. An effort regarding public communication seems necessary in order to reassure the population. The study of other media, such as the Internet, could help to deepen this study.